2010
DOI: 10.1007/s11033-010-0607-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Toll-like receptors 3 (c.1377C/T) and 9 (G2848A) gene polymorphisms in cervical cancer susceptibility

Abstract: Cervical cancer is emerging as a leading cause of morbidity and mortality in women worldwide. Toll-like Receptor (TLR) gene polymorphisms may contribute to subsequent inter-individual variability in cancer susceptibility. The present study aimed to identify the role of TLR 3 (c.1377C/T) [rs3775290] and TLR 9 (G2848A) [rs352140] gene polymorphisms in the risk of developing cervical cancer in North India. Peripheral blood samples were collected from 200 histopathologically confirmed cervical cancer patients from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
70
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 29 publications
1
70
0
1
Order By: Relevance
“…The study populations in the 19 included articles consisted of 9 Asian and 10 Caucasian studies. The distribution of genotypes in the controls of all included studies was consistent with Hard-Weinberg equilibrium except for the studies conducted by Mandal et al (2012), Pandey et al (2011), and Lai et al (2013). Detailed characteristics of the included studies are summarized in Table 1.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 71%
See 3 more Smart Citations
“…The study populations in the 19 included articles consisted of 9 Asian and 10 Caucasian studies. The distribution of genotypes in the controls of all included studies was consistent with Hard-Weinberg equilibrium except for the studies conducted by Mandal et al (2012), Pandey et al (2011), and Lai et al (2013). Detailed characteristics of the included studies are summarized in Table 1.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 71%
“…However, to date, no studies have demonstrated significant associations between this SNP and breast (Etokebe et al, 2009;Resler et al, 2013), bladder (Singh et al, 2013), prostate (Mandal et al, 2012), colorectal (Li et al, 2009), and cervical cancers (Pandey et al, 2011;Lai et al, 2013), except for one study, which reported an increased risk for cervical cancer (Roszak et al, 2012). Consistent with most of these individual studies, in this meta-analysis incorporating 11 case-control studies with 3775 cases and 3769 controls, we found no significant evidence supporting an association between cancer risk and the rs352140 polymorphism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cervical cancer data from the most relevant published articles and the doctoral dissertation original research conducted by the author at a premier medical research Institute (Sanjay Gandhi Post Graduate Institute of Medical Sciences) in Lucknow, India demonstrated that sample size numbers were 150 cases/150 controls , 200 cases/200 controls (Pandey et al, 2010), 200 cases/200 controls (Pandey et al, 2011), thereby highlighting homogeneity in the sample cohort data set(s). The total number of clinical samples, including patients and normal healthy study subjects were ≤400 in most of the studies, thus demonstrating the adequacy in sample size and the quality time invested in initial questionnaire-based face to face patient interviews and subsequent clinical specimen collection in collaboration with and/or supervision of the clinical experts/radiation oncologists.…”
Section: Literature Reviewmentioning
confidence: 99%